(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article is devoted to the study of the relationship between the family, the mahalla and educational institutions in the process of teaching foreign languages. Analyzing the theoretical foundations and empirical data, the work identifies the key factors contributing to the formation of the language environment and motivation of students. An innovative model of cooperation between all stakeholders proposed to improve the effectiveness of teaching foreign languages.